The effect of Benson's relaxation and mindfulness on the sleep quality of pregnant women: A randomized clinical trial study - Fatemeh Shams; Shaghayegh Moradi Alamdarloo; Mohammad Malekzadeh; Mohammadlatif Rastian (Mashhad University of Medical Sciences, 2023)
Introduction: Pregnant women due to hormonal and physical changes in pregnancy face many problems, such as sleep disorders, which creates stress, tension and anxiety. Due to limitation of drug consumption during pregnancy, it is possible to use non-pharmacological methods to improve this situation, which can point to Benson's relaxation and mindfulness. Therefore, the present study was conducted with aim to determine and compare the effect of Benson's relaxation and mindfulness on the sleep quality of pregnant women. Methods: : In this single-blind randomized clinical trial study which was conducted in 2022, 102 pregnant women from Shiraz city with low sleep quality were allocated to one of the three groups of Benson relaxation, mindfulness and control by using the random block allocation method. The data related to the quality of sleep was checked through the Pittsburgh questionnaire before and one month after the intervention. The interventions were carried out in 8 weeks. Data were analyzed using SPSS software (version 21) and Chi-square, ANOVA, Tukey's post hoc test and paired t-test. P<0.05 was considered statistically significant. Results: Before the intervention, there was no statistically significant difference among the three groups in the mean score of sleep quality (P >0.05). The mean total scores of sleep quality before the intervention in the three groups of Benson's relaxation, mindfulness and control were 7.08±1.83, 7.52±2.77 and 6.76±2.27, respectively, and after the intervention were 3.52±3.23, 2.73±2.24 and 6.91±2.19, respectively; there was a significant difference between the two intervention groups and the control group after the intervention (p<0.05) and both two intervention groups had the same effect compared to the control group. Conclusion: Both methods of Benson relaxation technique and mindfulness are effective on the sleep quality of pregnant women; therefore both methods can be used as the care intervention.